Case series on high grade appendiceal cancer with peritoneal and liver carcinomatosis undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC). (May 2022) - Roy, Susmit Prosun; Al Zhahrani, Nayef; Barat, Shoma; Morris, David L.
Abstract: Background: Pseudomyxoma Peritonei (PMP) is a mucin producing cancer with appendix as primary site. Cytoreductive Surgery (CRS) combined with hyper-thermic intraperitoneal chemotherapy (HIPEC) is an established form of therapy known to prolong survival in patients with PMP and peritoneal carcinomatosis. Methods/patients In our case series, we present five cases of PMP with synchronous liver and peritoneal metastasis treated with CRS and HIPEC. It is a very rare condition which needs more research to be able to comment on overall survival. Results: However, in our study, we found lower age, female gender and complete cytoreduction in surgery to be favourable predictors for improved morbidity. Conclusion: In our experience, CRS/HIPEC seem to be feasible for patients with PMP with synchronous liver and peritoneal metastasis. Highlights: High Grade synchronous Appendiceal cancer metastatic to liver and peritoneum No specific management guidelines exist. Cytoreductive surgery and Hyperthermic Intraperitoneal Chemotherapy seem to be safe No known studies looking at CRS and HIPEC for these patients. Extremely rare condition